2011
DOI: 10.1186/1471-2458-11-838
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve work outcomes in work-related PTSD: a systematic review

Abstract: BackgroundPosttraumatic stress disorder acquired at work can be debilitating both for workers and their employers. The disorder can result in increased sick leave, reduced productivity, and even unemployment. Furthermore, workers are especially unlikely to return to their previous place of employment after a traumatic incident at work because of the traumatic memories and symptoms of avoidance that typically accompany the disorder. Therefore, intervening in work-related PTSD becomes especially important in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 24 publications
2
51
0
1
Order By: Relevance
“…The results of the search and review process are shown in Fig. 1 via Stergiopoulos et al (2011). After removing 107 duplicates, 242 publications were screened on the basis of title and abstract, of those 10 had an English abstract but were written in a different language.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the search and review process are shown in Fig. 1 via Stergiopoulos et al (2011). After removing 107 duplicates, 242 publications were screened on the basis of title and abstract, of those 10 had an English abstract but were written in a different language.…”
Section: Resultsmentioning
confidence: 99%
“…An 8-item quality assessment checklist was developed a priori to assess the methodological quality of the included studies adapted from a previous checklist used by Stergiopoulos et al (2011) [45]. Assessment questions examined study design, methods, measurements, analysis and data presentation.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the rehabilitation of mentally injured workers appears essential to enable employees to return to work. A recent review noted the lack of research on interventions for work-related PTSD [32]. Thus, the current paper aims to examine the evolution of symptoms and QoL throughout CBT for PTSD in individuals exposed to workplace trauma.…”
Section: Introductionmentioning
confidence: 99%